Syntactic priming in Chinese sentence comprehension: Evidence from Event-Related Potentials - Chen, Qingrong; Xu, Xiaodong; Tan, Dingliang; Zhang, Jingjing; Zhong, Yuan (Brain and cognition, 2013)
•This is the first report that provides electrophysiological evidence of syntactic priming in Chinese.•Priming effects were robust when the verb was repeated.•The P600 amplitude was reduced in repeated target sentences at the word de.•No significant effects were observed in target sentences with synonymous conditions. Using the event-related potential (ERP) technique, this study examined the nature of syntactic priming effects in Chinese. Participants were required to read prime-target sentence pairs each embedding an ambiguous relative clause (RC) containing either the same verb or a synonymous verb. In Chinese, the word de serves as a relative clause marker. During reading a potential Chinese RC structure (either the prime or the target sentence), Chinese readers initially expect to read an Subject–Verb–Object (SVO) structure but the encounter of a relative clause marker de would make readers abandon the initial strategy and reanalyze the structure as a relative clause. A reduced P600 effect was elicited by the critical word de in the target sentence containing the same initial verb as in the prime sentence. No significant reduction of the P600 was observed in the target sentences in the synonymous condition. The results demonstrated that verb repetition but not similarity in meaning produced a syntactic priming effect in Chinese. The constraint-based lexicalist hypothesis and the argument structure theory were adopted to explain the syntactic priming effect obtained in the current study.